Evolution of Frieswal cattle: A crossbred dairy animal of India - KUMAR, SUSHIL; ALEX, RANI; GAUR, G K; MUKHERJEE, S S; MANDAL, D K; SINGH, UMESH; TYAGI, S; KUMAR, ARUN; DAS, A K; DEB, RAJIB; KUMAR, MAHESH; SIROHI, A S; et al. (The Indian Journal of Animal Sciences, 2018)
Frieswal cattle is one of the crossbred strains having 5/8 Holstein Friesian and 3/8 Sahiwal inheritance, develo pedby ICAR-Central Institute for Research on Cattle, Meerut, in collaboration with Ministry of Defence. The projectwas started in 1987 for the evolution of a new crossbred national milch breed: Frieswal â€“ (HolsteinÃ—Sahiwal), yielding 4,000 kg of milk with 4% butter fat in a mature lactation of 300 days. It is the only project in the country where such a huge population of animals (more than 20,000) is available with accurate production and pedigree records of each and every animal over generations, with well-established progeny testing network in 37 military farms to cover all the agro-climatic zones of the country. In this review, an attempt has been made to analyze the genesis, present status and future prospects of Frieswal cattle in India.